(3GdeaGgje GdMOjKI dEOGQI GdEfJGL hGdYedjGJ (B/s - (3jMjGhj, eajOIs; (3SWMGhj, YRjRs; (3jMjGhj, EdgGes ((3YeGf(B: s (3OGQ CSGeI ddfTQ hGdJhRjY(B; (3fHdGA fGTQhf hehRYhf (B, s, 2014)
(3jVe eONd Edi EOGI GdEfJGL hGdYedjGJ, GdJYbjO hGddGjbjf aj EOGQI GdEfJGL, GdCOGA hcjajGJ JMSjfg HGdeDSSGJ GdUfGYjI hGdJfHD HGdeHjYGJ, EOGQI GdeNRhf hJNWjW QbGHI GdEfJGL, GdfXGe GdCeQjcj(B(MRP) (3hGdfXGe GdjGHGfj(B(JIT) (3aj EOGQI GdEfJGL hfXGe JcfhdhLjG GdEfJGL GdCeKd (BOPT(3, EOGQI GdLhOI aj GdeDSSGJ GdUfGYjI hJcfhdhLjG GdeYdheGJ aj EOGQI GdEfJGL(B.s
(3HHdjhZQGajG(B: (3U(B.317-328 s
Keywords: (3EOGQI GdEfJGLs; (3EOGQI GdEfJGL(B- (3GdJcfhdhLjGs; (3HMhK GdYedjGJs